Role of E-Scaffolding in Inquiry based-Flipped Classroom Toward High School Students Scientific Reasoning in Physics - Yana, Annisa Ulfa; Handayanto*, Supriyono Koes; Taufiq, Ahmad; Rizal, Fauzul (Jurnal Pendidikan Sains Indonesia, 2025)
High school physics education in Indonesia requires a strong foundation in scientific reasoning, especially when it comes to adapting to post-covid 19 learning innovations. Therefore, this study aims to determine how e-scaffolding influences high school students' scientific reasoning when integrated into inquiry-based flipped physics classrooms (E-IFPC) compared to inquiry-based flipped classrooms (IFPC) without e-scaffolding. This research is quasi-experimental educational research. The scientific reasoning of students was assessed using a validated 13 two-tier scientific reasoning test (=0.901). Data analysis included independent t-tests and normalized Gain (N-Gain) calculations to evaluate the research hypothesis. The results showed significant differences in scientific reasoning between the E-IFPC and IFPC groups. . Students in the E-IFPC group exhibited a N-Gain score of G=0.43, which was nearly five times higher than the G=0.09 observed in the IFPC group. This reaseach contribute to the field of physics education by providing empirical evidence of significant impact of e-scaffolding on enhances the scientific reasoning of high school students in physics, particulary in the context of post-pandemic learning innovation